Studies Regarding the Antimicrobial Behavior of Clotrimazole and Limonene - Verginica Schroder; Nicoleta Radu; Petruta Calina Cornea; Oana Andreia Coman; Lucia Camelia Pirvu; Mohammed Shaymaa Omar Mohammed; Amalia Stefaniu; Lucia Pintilie; Marinela Bostan; Mihai Dan Caramihai; Viviana Roman (MDPI AG, 2022)
The paper presents the results of the studies performed to establish the effect of the mixtures between limonene and clotrimazole against microbial pathogens involved in dermatological diseases, such as Candida albicans, Staphyloccocus aureus, and Escherichia coli. Preliminary data obtained from the studies performed in microplates revealed a possible synergism between the mixture of clotrimazole and limonene for Staphylococcus aureus. Studies performed "in silico" with programs such as CLC Drug Discovery Workbench and MOLEGRO Virtual Docker, gave favorable scores for docking each compound on a specific binding site for each microorganism. The tests performed for validation, with the clotrimazole (0.1%) and different sources of limonene (1.9% citrus essential oils), showed a synergistic effect on Staphylococcus aureus in the case of the mixtures between clotrimazole and the essential oils of Citrus reticulata or Citrus paradisi. The studies performed on Staphylococcus aureus MRSA showed a synergistic effect between clotrimazole and the essential oils obtained from Citrus bergamia, Citrus aurantium, or Citrus paradisi. In the case of Pseudomonas aeruginosa, essential oils and clotrimazole used alone did not exhibit antimicrobial activities, but the mixtures between clotrimazole and the essential oils of Citrus bergamia or Citrus sinensis exhibited a synergistic antimicrobial effect.